Discovery of a small-molecule inhibitor of STAT3 by ligand-based pharmacophore screening - Leung, Ka-Ho (2016)
STAT3 modulates the transcription of a wide variety of regulatory genes involved in cell proliferation, differentiation, migration, apoptosis, and other critical cellular functions. Constitutive activation of STAT3 has been detected in a wide spectrum of human malignancies. A pharmacophore model constructed from a training set of STAT3 inhibitors binding to the SH2 domain was used to screen an in-house database of compounds, from which azepine 1 emerged as a top candidate. Compound 1 inhibited STAT3 DNA-binding activity in vitro and attenuated STAT3-directed transcription in cellulo with comparable potency to the well-known STAT3 inhibitor S3I-201. A fluorescence polarization assay revealed that compound 1 targeted the SH2 domain of STAT3. Furthermore, compound 1 inhibited STAT3 phosphorylation in cells without affecting the total expression of STAT3. This study also validates the use of pharmacophore modeling to identify inhibitors of protein–protein interactions.